Produção de fosfatases ácidas por Trichoderma harzianum em fermentação sólida - Afonso, Jussara Maria Martins de Almeida (2022)
The absorption of phosphorus from the environment and its efficient use require the action of a large class of enzymes called phosphatases. These enzymes are widely distributed in plants, animal cells and microorganisms. Fungi are able to convert insoluble phosphorus into soluble forms during acidification and chelation processes, or even by hydrolysis mediated by phosphatase enzymes. According to their optimal pH of activity, phosphatases can be classified as acid phosphatase (ACPases), where their pH is less than 6.00. In this context, the present work evaluated different forms of cultivation and extraction of acid phosphatases through solid fermentation (FES) and submerged fermentation (FSbm) using the fungus Trichoderma harzianum and millet, wheat bran and soybean meal as sources of phosphates. Preliminary tests were fundamental to analyze the enzyme production potential of the Trichoderma harzianum strain, the results were for the fermentation millet studied with the different forms of cultivation and the enzymatic selection.Thus, through Central Composite Planning, it was possible to develop equations for acid phosphatase activity (U/mL) and dry biomass (g/L) using as parameters: millet mass, inoculum, and moisture. The best results were for the solid fermentation, using the millet substrate with cultivation in sterile distilled water and extraction with tween 80, where there was a growth of cell biomass, and enzymatic activity, whose average final values were 9.78 ± 3.68 g/L and 36.67 ± 12.24 U/mL, respectively, after 9 days of solid fermentation.